"1+1>2": Highly efficient removal of organic pollutants by composite nanofibrous membrane based on the synergistic effect of adsorption and photocatalysis. (10th October 2022) - Xu, Yuanting; Lin, Wanting; Yuan, Dandan; Chen, Shifan; Li, Fang; Long, Yanping; He, Chao; Zhao, Weifeng; Zhao, Changsheng
Highlights: A dual-functional nanofibrous membrane material was prepared for wastewater remediation. The adsorption facilitated and accelerated the photocatalytic degradation reaction. The photocatalysis regenerated the adsorption active site and realized green recycle. The synergistic effect of adsorption and photocatalysis was investigated systematically. The synergy produced a "1+1>2" effect for highly efficient removal of pollutants. Abstract: Adsorption and photocatalysis are regarded as two desirable technologies for wastewater remediation, but are still unsatisfactory in removal effect, eco-friendly regeneration and facile reusability. In this study, we developed a composite nanofibrous membrane material with excellent removal performance for organic pollutants based on synergistic adsorption and photocatalysis. A novel boron-doped, nitrogen-deficient graphitic carbon nitride (B-C3 N4 ) photocatalyst as well as an amphiphilic copolymer of methyl methacrylate and acrylic acid (p(MMA-AA)) were synthesized respectively, and then used to modify polyethersulfone for the fabrication of composite nanofibrous membrane with improved hydrophilicity, negatively-charge property and enhanced visible light response simultaneously. Subsequently, the synergistic effect of adsorption and photocatalytic degradation for organic pollutants were identified especially and resulted in an excellent removal efficiency even superior to the combination of adsorption and photocatalytic degradation, which could be called a "1+1>2" effect. In addition, the regeneration and reusability, the purification ability for multicomponent wastewater, and the photocatalytic mechanism, were investigated and discussed systematically. In this work, we not only prepared the nanofibrous membrane with synergistic effect of adsorption and photocatalysis, but also provided a versatile approach to design dual-functional support material to ensure the practical applications of powdery photocatalyst in wastewater treatment.